PENGARUH TERAPI MBSR TERHADAP TEKANAN DARAH DAN TINGKAT STRESS PADA PENDERITA HIPERTENSI - Aliftitah, Sugesti; Oktavianisya, Nelyta (Jurnal Ilmiah Kesehatan, 2025)
Hypertension patients must routinely take hypertension medication, control blood pressure and change lifestyles that are at risk of worsening hypertension. This condition sometimes causes stress for hypertension patients. The study aims to determine the effect of Mindfulness-Based Stress Reduction (MBSR) therapy on blood pressure and stress levels in hypertension patients in Bluto. The research design was analytical with a one group pre-posttest design. This study involved 32 respondents with a sampling technique of simple random sampling. The instrument for measuring blood pressure was a sphygmomanometer and to measure stress level used the Perceived Stress Scale (PSS) questionnaire. The test used was the Wilcoxon test. The results showed that blood pressure after MBSR therapy in most respondents decreased compared to blood pressure before MBSR therapy were 18 respondents (56.25%). The stress level after MBSR therapy in hypertension patients was mostly in the moderate category namely 19 respondents (59.4%). The results of the pretest-posttest data analysis of blood pressure and stress levels using the Wilcoxon test were the same, with ρValue = 0.000 and α = 0.05. Because ρValue <α, there is an effect of MBSR therapy on blood pressure and stress levels in hypertension patients in Bluto. MBSR therapy expectedly can reduce blood pressure and stress levels in hypertension patients.